Big dilemma in face mask consumption: environmental sensitivity versus the fear of COVID-19 - Aydin, Kenan; Yildirim, Seda; Cizer, Ece Ozer (INDERSCIENCE ENTERPRISES LTD, 2023)
The COVID-19 pandemic has created a significant transformation in the production and consumption of face masks. This study investigated the main indicators that affect attitude and intention toward reducing unnecessary face mask consumption during the COVID-19 pandemic. Accordingly, this study focused on exploring how environmental sensitivity, the fear of COVID-19, price sensitivity, and subjective norms influence mask consumption behaviour based on the theory of planned behaviour (TPB). The data was collected from Turkish citizens by survey method. As a result, it was seen that environmental sensitivity, price sensitivity, and subjective norms affected attitude and intention towards reducing unnecessary mask consumption positively. On the other side, it was determined that fear of COVID-19 increased face mask usage and affected attitude and intention towards reducing unnecessary mask consumption negatively.
Keywords: environmental sensitivity; fear of COVID-19; subjective norms; price sensitivity; face mask consumption; PLANNED BEHAVIOR; GREEN HOTEL; INTENTION; Environmental Sciences & Ecology